ANALISIS KOMPOSISI KOMPOSIT POLIPROPILEN/KARBON AKTIF TERHADAP KEKUATAN BENDING UNTUK APLIKASI PLAT DWIKUTUP FUEL CELL - Iswandi Iswandi; Muhammad Idris; Indra Hermawan; Yopan Rahmad Aldori; Muhammad Irwanto (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2022)
Carbon-based material is one of the main filler materials for the manufacture of polymer composite bipolar plates for fuel cell applications. Some variation materials filler based carbon used on manufacture bipolar plate white high cost.  Determine of low cost filler materials is one of special issue for manufacture bipolar plate. Activated carbon is a alternative for suitable filler material base carbon at polymer composite and easy to find in Indonesia. This study investigates the effect of activated carbon composition in polymer composites on bending strength with a composition of 10, 20, 30, 40 (percent by weight) activated carbon (AC) with a polypropylene (PP) matrix. The sample has fabricated used hot press mouding with mix process at 220o C temperatures with 320 Psi pressure in 20 minutes. The bending test results with the standard three point bending test ASTM D790-03, The best value was found at a composition of 10% by weight of activated carbon of 26.9 MPa. This achievement has been obtained the Department of Energy, United State Of America (DOE USA) standard is 25 Mpa. This condition due to the polymer's composition of 10% KA to 90% PP, which makes it easier for the polymer to yield higher bonding and hence boost bending strength.